Potential Anionic Substances Binding to Platelet Factor 4 in Vaccine-Induced Thrombotic Thrombocytopenia of ChAdOx1-S Vaccine for SARS-CoV-2 - Pang, Xiaocong; Liu, Haitao; He, Xu; Ji, Tianrong; Zhu, Yizhun; Cui, Yimin (Frontiers in Immunology, 2022)
Recent reports of the rare ChAdOx1 nCoV-19 vaccine-related venous thrombosis led to a worldwide suspension of its usage. Vaccine-induced thrombotic thrombocytopenia (VITT) is characterized by thrombocytopenia and thrombosis in association with anti-PF4 antibodies. Herein, we propose five potential anionic substances of ChAdOx1 nCoV-19 vaccine that can combine with PF4 and trigger VITT, including (1) the proteins on the surface of adenovirus, e.g. negative charged glycoprotein, (2) the adjuvant components of the vaccine, e.g. Tween 80, (3) the DNA of adenovirus, (4) the S protein antigen expressed by the vaccine, (5) the negative charged impurity proteins expressed by the vaccine, e.g. adenovirus skeleton proteins. After analysis of each case, we consider the most possible one is the negative charged impurity proteins expressed by the vaccine. Then, we display possible extravascular route and intravascular route of the formation of PF4 autoantibodies triggered by the negative charged impurity proteins，which is accordant with clinical situation. Accordingly, the susceptible individuals of VITT after ChAdOx1 nCoV-19 vaccination may be those people who could express the negative charged impurity proteins and reach a certain high titer.